Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Bina Media Tenggara Jakarta Pusat - Zahra, Dimah Zahrah Nur Aidah; Lahat, Mohammad Amas; Utama, Dani Chandra (CV Warnak Johanna Nusantara, 2025)
Many internal and external factors can affect the results of an organization's efforts to improve employee performance. Work motivation and discipline are two important components and have a major impact on employee performance. This study aims to explain the partial and simultaneous influence between work motivation and work discipline variables on employee performance at PT Bina Media Tenggara. This type of research uses quantitative techniques and uses survey methodology and special sampling strategies to select respondents and then send questionnaires to employees with the sampling technique used, namely saturated samples. The statistical software used is SPSS version 26, in this study there were 40 employees who were employees of PT Bina Media Tenggara. The results of the partial t-test with a significance value of 0.000 < 0.05 indicate that work motivation and work discipline affect employee performance positively and statistically significantly. The results of the Simultaneous F test with a calculated F value of 103.105 with an F value in the table of 3.24 and a significance value of 0.000 < 0.05 indicate that work motivation and work discipline both have a positive and significant influence on employee performance.